Growth Performance and Survivability of Rajasree Birds under Deep Litter and Scavenging Systems - Krishna, Daida; Ramarao, S.V.; Prakash, B.; Preetham, V. Chinni (International Journal of Poultry Science, 2012)
The aim of the experiment was to determine the performance and survivability of Rajasree birds under backyard condition. A total number of 2000 day old chicks of Rajasree were reared in deep litter house up to 9 weeks under controlled conditions to record the body weight, feed consumption and feed conversion ratio. After 9 weeks, 1800 birds were equally distributed to 60 beneficiaries (20 females and 10 males) in four villages of Nalgonda district of Andhra Pradesh to record the body weight, feed consumption and feed conversion ratio under the backyard condition up to 20 weeks. At the age of day old, the average weight of male and female chicks was 33 and 30 g, respectively. The male and female average body weight gains and feed consumption at 9th week were 582 and 491 g and 1868 and 1951 g, respectively. The feed conversion ratio at 9th week was 3.20 and 3.97 respectively. The average mortality was 3.12% up to 9 weeks. The male and female mean body weight at 20th week were 1160.7 and 1006.9 g under backyard farming. The body weights were significantly (p<0.05) greater for birds reared in Shaligouraram (1204 g and 1023 g) and Chilkur village (1196 g and 1024 g) compared to other two villages. Therefore, it has been concluded that the 10-15% of supplementary feeding will optimize the performance of the birds under backyard condition, which will surely lead to increase the nutritional security and livelihood of under privilege sections of the society.